Efficiency Evaluation of Two Media for In Vitro Maturation of Buffalo Oocytes - Patel, Parth S.; Suthar, Vishal S.; Suthar, Babulal N.; Patil, Deepak B.; Joshi, Chaitanya G. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was conducted to evaluate morphometry of ovarian functional structures and effect of two different commercially available in vitro maturation (IVM) media on cytoplasmic and nuclear maturation of slaughter origin buffalo oocytes. The buffalo ovaries were collected from Ahmedabad Municipal slaughter-house, Ahmedabad and were transported at the laboratory within 2-3 h of slaughter at 33 to 35°C warm normal saline. The ovaries were washed and processed under laminar floor and evaluated for functional structures like mature corpus luteum (CL) and follicles i)
Keywords: Buffalo; Cumulus oocytes complexes; In vitro maturation; Media